A note on efficiency of rockets - Gupta, S. K.; Mehta, A. K. (Defence Science Journal, 2013)
The paper discusses the dependence of efficiency of a rocket on the expansion ratio and the ratio of the initial mass of the rocket and the mass of the propellant. The relation is illustrated by a table and two graphs.